Social, Economic, Cultural and Environmental Diagnosis of the Páez Jerusalén Indigenous Council of the Municipality of Santander de Quilichao, Cauca, Colombia - Ramírez Martínez, Miguel Ángel; Menza Ulcue, Soli Yined; Olaya García , María Fanny (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To elaborate a social, economic, cultural and environmental diagnosis of the Páez Jerusalén indigenous cabildo of the municipality of Santander de Quilichao, Cauca, Colombia.MATERIAL AND METHOD: It is an exploratory research, with a mixed approach. A questionnaire was applied to 180 families, containing four dimensions: social, economic, cultural and environmental.RESULTS: We found: 1) That agriculture is the main source of income of the community, 2) There is a high marginalization and poverty: 3) There is a maintenance of their language, customs and traditions, and 4) There is an increase of pollution due to the lack of ecological education.CONCLUSIONS: With this diagnosis, the bases are laid for the realization of a community development plan that, when implemented, would improve the quality of life of the community.
Keywords: Economy; Society; Culture; Environment; Community strategic planning.